2022
DOI: 10.14202/vetworld.2022.962-967
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous expression of the gene of KI67 and P53 in cynomolgus monkeys infected with papillomavirus

Abstract: Background and Aim: Cynomolgus monkeys (Macaca fascicularis) develop spontaneous infection of Papillomavirus (PV); thus, potentially beneficial for modeling human PV (HPV) infection study. Contrary to human origin, infection in cynomolgus monkeys does not always show evident clinical symptoms of cervical cancer. The absence of cervical cancer clinical symptoms leads us to investigate the molecular mechanism of the HPV infection in cynomolgus monkeys. This study aimed to investigate the messenger ribonucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In addition, all higher-grade lesions most commonly arise at the squamocolumnar junction, the predominant target site for oncogenic HPVs. 3,13 Study in three baboons (Papio hamadryas anubis) showed a dysplastic proliferative changes that consistent with cervical squamous intraepithelial neoplasia (CIN) as same as in human. 21 Here, we show that the majority of MfPV3 infected monkeys have detectable CIN and moderate to high degree of ITGα6 expression in both uterine and cervical organ tissues, while MfPV3negative monkeys show low levels of ITGα6 expression and no detecatble CIN.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, all higher-grade lesions most commonly arise at the squamocolumnar junction, the predominant target site for oncogenic HPVs. 3,13 Study in three baboons (Papio hamadryas anubis) showed a dysplastic proliferative changes that consistent with cervical squamous intraepithelial neoplasia (CIN) as same as in human. 21 Here, we show that the majority of MfPV3 infected monkeys have detectable CIN and moderate to high degree of ITGα6 expression in both uterine and cervical organ tissues, while MfPV3negative monkeys show low levels of ITGα6 expression and no detecatble CIN.…”
Section: Discussionmentioning
confidence: 89%
“…Sequence comparisons and phylogenetic analyses indicate that these novel MfPVs cluster together within the alpha12 PV species closely related to the alpha 9 (e.g., HPV16) and alpha11 species (e.g., HPV34). 12 Futhermore, Darusman et al 13 obtained result that PV infected cynomolgus monkeys shown increased expression of messenger ribonucleic acid (mRNA) gen KI67 and decreased expression gen P53 compared to non-infected monkeys. KI67 and P53 known as biomarker of oncogenesis of PV Infection, and this discovery indicates that MfPV and HPV have a shared pathogenic mechanism.…”
mentioning
confidence: 99%
“…Meanwhile, TAD2 is the second and plays a role in the transcriptional activation of RPA proteins. These sub‐domains are essential constituents of p53 due to their function as tumor suppressors and degradation as well as activity during cellular stress conditions 61,62 . Apoptosis can be controlled by proto‐oncogenes and the superior cancer protein p53 , 63 namely the guardian of the genome , which can induce apoptosis and autophagy in various cancer cells 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…These sub-domains are essential constituents of p53 due to their function as tumor suppressors and degradation as well as activity during cellular stress conditions. 61,62 Apoptosis can be controlled by proto-oncogenes and the superior cancer protein p53, 63 namely the guardian of the genome, which can induce apoptosis and autophagy in various cancer cells. 64,65 p53 also inhibited the formation of cancer cells and DNA damage through the regulation of target genes, which play a role in cell cycle arrest, DNA repair, or apoptosis.…”
Section: Vero Cell Linementioning
confidence: 99%
“…A prior study has undertaken ICA injection in rats with tumors, the use of non-human primate/NHP animal models can be explored considering the genetic similarities of NHP to humans. 4,5…”
Section: Dear Editormentioning
confidence: 99%